DOI: 10.18174/459129
|View full text |Cite
|
Sign up to set email alerts
|

Do multi-stakeholder platforms work? : contributions of multi-stakeholder platforms to the performance of research for development interventions

Abstract: Discussion and way forward | 46 3 Social network analysis of multi-stakeholder platforms in agricultural research for development: Opportunities and constraints for innovation and scaling | 51 Abstract | 52 3.1 Introduction | 53 cult days. I also thank Prof. Leeuwis, Dr. Piet van Asten, and Dr. Bernard Vanlauwe for their leadership and guidance during these days. Finally, I would like to thank the amazing research support team of the Wageningen University Communication, Philosophy, and Technology Unit. Vera Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 168 publications
(430 reference statements)
2
2
0
Order By: Relevance
“…The negative correlation between centralization and innovation behavior means that as actors perceive powers to be centralized, their capacity to generate and implement new ideas in limited. This finding is in agreement with recent findings by Sartas (2018) who confirmed that centralization of innovation networks may inhibit innovation and scaling since it crowds out some important stakeholders from policy space. Previous studies by Uzzi (1997) In addition to network size, number of ties and the structural position of actors in the network, personal relationships that develop through interactions were noted to be important determinants of innovation behavior.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The negative correlation between centralization and innovation behavior means that as actors perceive powers to be centralized, their capacity to generate and implement new ideas in limited. This finding is in agreement with recent findings by Sartas (2018) who confirmed that centralization of innovation networks may inhibit innovation and scaling since it crowds out some important stakeholders from policy space. Previous studies by Uzzi (1997) In addition to network size, number of ties and the structural position of actors in the network, personal relationships that develop through interactions were noted to be important determinants of innovation behavior.…”
Section: Discussionsupporting
confidence: 93%
“…According to Burt (1992) and Uzzi (1996), as actor connections increase in a network, more information flows between each of the players which results into trust and joint problem-solving arrangements within the network. The findings are also in agreement with scholars such as Gulati (1998); Li et al (2013); Sartas (2018) who assert that the layout of a network in terms of ties and connections between actors measures the actor's involvement in decision making processes and consequently the flow of resources and innovation. They argue that actors with more connections are more likely to implement innovations than their counterparts.…”
Section: Discussionsupporting
confidence: 90%
“…Our focus is on the role and potential of MSPs to contribute to transformative change as a deliberate, inclusive, and accountable response to deficiencies in natural resource governance, positioning actors and institutions as key forces both responding to the governance context and capable of instigating change within it (Giddens 1984, Olsson et al 2008. This is not to imply that MSPs necessarily yield such results (Warner 2007, Sartas 2018). Rather, it sharpens the focus on comparative analysis to understand the ways in which MSPs in practice affect stakeholder relationships and behaviors.…”
Section: Comparative Framework and Research Methodsmentioning
confidence: 99%
“…Innovation platforms are considered to be social networks and informal partnerships that are guided by informal social systems rather than by bureaucratic structures and formal contractual relationships. Because of this characteristic, they are seen as a promising avenue for finding solutions to complex social, economic and environmental challenges that face agricultural innovation stakeholders such as farmers, development practitioners and policymakers (Sartas, 2018;Kilelu et al, 2013). It is argued that innovation platforms increase collaboration, exchange of knowledge and influence mediation among multiple actors thereby enhancing their capacity to innovate and scale up the actor innovation behaviour (Hermans, Sartas, van Schagen, van Asten & Schut, 2017).…”
Section: Introductionmentioning
confidence: 99%